Analisis Faktor Alami dan Antropogenik Banjir di ASEAN serta Strategi Peningkatan Literasi Bencana Banjir Siswa SD: Kajian Literatur - Pradela Maynafia Wahani; Sutarno (Advances In Education Journal, 2025)
Floods in ASEAN are triggered by the interaction of extreme natural factors (tropical cyclones, typhoons) and dominant anthropogenic factors (land-use change, environmental degradation). This study analyzes the complexity of flood-triggering factors across the region and formulates effective strategies for strengthening flood disaster literacy among Elementary School (ES) students. Literature review results indicate that literacy enhancement must be holistic, covering cognitive, affective, and psychomotor domains, and based on contextual regional risk data. Effective methods include child-friendly techniques like storytelling, utilizing local maps, and adopting technology-based learning applications. The novelty lies in proposing a Regional Risk-Based Curriculum Model, bridging macro-level threat analysis with micro-level educational practice. The ultimate goal is to develop ES students as vigilant and responsible mitigation agents.